Thyrotoxicosis Due to Acute Suppurative Thyroiditis in a Pediatric Patient: A Case Report - Lara McHan MD; Jyotsna Gupta MD (SAGE Publishing, 2022)
Acute suppurative thyroiditis is a rare and potentially life-threatening cause of thyroid inflammation requiring prompt recognition and management. There are few reported cases of thyrotoxicosis due to acute suppurative thyroiditis. We are reporting the case of a 9-year-old boy who presented to the emergency room with fevers, neck pain and swelling, night terrors, and emotional lability. He was hemodynamically stable with initial lab work remarkable for neutrophilia without leukocytosis, elevated inflammatory markers, and hyperthyroidism. Imaging of the neck revealed a heterogenous collection in the region of the left thyroid concerning for suppurative thyroiditis and adenitis. He was admitted to the hospital and initiated on intravenous antibiotics. Given lack of significant improvement in pain, he was taken to the operating room for drainage on hospital day 4 with remarkable clinical improvement in pain. He was discharged on oral antibiotics. Lab work obtained on postoperative day 15 showed resolution of hyperthyroidism and decreasing inflammatory markers. Subsequent imaging following resolution of the acute illness did not reveal any anatomic abnormality that may have predisposed him to developing acute suppurative thyroiditis. Thyrotoxicosis as a complication of acute suppurative thyroiditis is a rare occurrence, and is thought to be due to the release of preformed thyroid hormone from damaged thyroid follicles. The thyrotoxic state is often transient and resolves with appropriate management of acute suppurative thyroiditis. This complication is important to recognize, as failure to appropriately diagnose and treat acute suppurative thyroiditis can lead to poor outcomes, such as airway compromise and death.